Upaya Meningkatkan Kunjungan Wisatawan Ke Yogyakarta Melalui Promosi Wisata Budaya Di Anjungan Daerah Istimewa Yogyakarta Taman Mini “Indonesia Indah” - Rahasti Rengganingsih; Yulianto - AKPAR BSI Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2012)
ABSTRACK - Efforts to increase tourist arrivals in the Pavilion area of Yogyakarta necessary and proper role of promotion in accordance with the development and progress of Yogyakarta. The analysis is based on theory and research in the field.The results showed that the pavilion Yogyakarta in Taman Mini "Indonesia Indah" design strategy using promotional mix is personal selling, with culture as a tourist destination and promotional materials. Furthermore, Platform Yogyakarta promotional package tailored to the objectives and delivery time, as well as the variety of media used so in the end this strategy can be achieved optimally.This study shows that the strategy has been carried out by the Regional Platform, is running as it should. But budget constraints still hamper the promotion and communication of tourism with local government activists still less harmonious, so that more promotiona boost from various fields. Therefore, the selection of appropriate promotional strategies to increase tourist visits to the pavilion Yogyakarta and Yogyakarta own course.Keywords: Tourist Arrivals, Promotion, Cultural Tourism, Wildlife Tourism